2004
DOI: 10.1530/rep.1.00087
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting developmental competence of equine oocytes after intracytoplasmic sperm injection

Abstract: This study was conducted to evaluate the effect of initial cumulus morphology (expanded or compact) and duration of in vitro maturation (24, 30 or 42 h) on the developmental competence of equine oocytes after intracytoplasmic sperm injection (ICSI). The effect of manipulation temperature (room temperature vs 37 8C) at the time of ICSI and concentration of glucose (0.55 vs 5.5 mM) during embryo culture was also investigated. The nuclear maturation rates of expanded (Ex) oocytes were significantly (P < 0.001) hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
(49 reference statements)
1
19
0
1
Order By: Relevance
“…We previously found high cleavage rates (69-94%) in equine zygotes cultured in the semidefined medium CZB-C ϩ BSA, with either low or high concentrations of glucose [9]. The average nucleus number at 96 h in that medium was also good, at 6.6-12.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We previously found high cleavage rates (69-94%) in equine zygotes cultured in the semidefined medium CZB-C ϩ BSA, with either low or high concentrations of glucose [9]. The average nucleus number at 96 h in that medium was also good, at 6.6-12.…”
Section: Discussionmentioning
confidence: 89%
“…Several laboratories have investigated the use of synthetic oviductal fluid (SOF)-based media, including commercial G1/G2 media, for equine embryo culture. We found that a modified Chatot, Ziomek, Bavister (CZB) medium (CZB-C) was capable of supporting equine embryo development in vitro for 4 days [8] and that glucose concentration in this medium (0.55 or 5.5 mM) did not affect development at 4 days [9], but embryos were not cultured further. Culture of injected oocytes for 7 days in G1.2/G2.2 yielded up to 9% blastocyst formation [3]; no difference was seen between change of medium at 3 or 4 days.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum duration of oocyte maturation for developmental competence has not been defined in the horse, and may vary according to oocyte cumulus type: we found that cleavage rates at 48-96 h after ICSI varied differentially with maturation duration for Ex and Cp oocytes [38]. Information is not available on the effects of ovary storage, cumulus type, or duration of oocyte maturation on blastocyst development in horses.…”
Section: Introductionmentioning
confidence: 84%
“…Briefly, after maturation, oocytes were denuded of cumulus by pipetting in 0.05% hyaluronidase and those with a polar body were used for ICSI. For ICSI with frozen-thawed (control) sperm, a swim-up procedure was used (Choi et al 2004). Briefly, semen was thawed at 37 8C for 30 s and 200 ml were layered under 1 ml Sp-CZB for swim-up.…”
Section: Icsimentioning
confidence: 99%
“…The basic techniques necessary to study this, including ICSI (Choi et al 2004) and in vitro embryo culture (Hinrichs et al 2005), are currently in place. Methods for activation of horse oocytes have been investigated; notably, these include injection of cytosolic extract, prepared from sperm via multiple cycles of flash freezing and thawing.…”
Section: Introductionmentioning
confidence: 99%